Fatores que influenciam a depreciação de veículos - Campos, Ana Paula Lucena (2013)
The study aims to analyze the behavior of the main factors that influence the depreciation of vehicles by assessing the profile of the car in the current scenario, estimating their percentage of financial loss and linking with existing variables in order to determine the characteristics of derogatory behavior. The research used a quantitative approach and through it seeks to deepen the topic addressed making it clearer and building issues important to the conduct of research. Thus, through the econometric method, values rose vehicles within three years, we identified the relationships between variables exist, ie, the characteristics of the car and identified the main factors that influence the depreciation to define type vehicle that has a higher loss. Finally, after analyzing the data will be presented findings on the characteristics of derogatory behavior and if it achieved satisfactory results.